Mind the Gap: Crowd-Funding and the Role of Seed Money - Joseph Deutsch; Gil S. Epstein; Alon Nir (Institute for the Study of Labor (IZA), 2015)
We analyze voluntary private contributions to public goods and the role seed money plays in signaling the public good's quality to potential subsequent contributors. We present a theoretical model and analyze two sets of naturally occurring data from crowd-funding platforms. After developing the theoretical background we find statistically significant switch points which distinguish between seed contributions to subsequent contributions. A positive change in contribution behavior after the switch suggests an increase in the perceived value of the public good. We find that the signal comprises the number of contributors and the average contribution (as proportion of targeted goal).
Keywords: H4; H42; H8; D8; 330; public goods; voluntary private provision; crowd-funding platform; seed money